2020
DOI: 10.1177/0972150920924506
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mediator in Examining the Influence of Antecedents of Mobile Wallet Adoption on Attitude and Intention

Abstract: The purpose of this article is to explore the mediating role of perceived usefulness, trust and attitude on a user’s intention towards use of mobile wallets in India. While mediation has been studied by earlier researchers in the context of online commerce, mobile banking, short message service (SMS) banking, mobile money, etc., not many studies exist in the context of mobile wallets. Considering the potential of mobile wallets in India, previous relationships from the theories of technology adoption like tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 50 publications
(80 reference statements)
5
55
1
Order By: Relevance
“…Our study found a significant relationship between PU and BI in line with the previous studies of Kumar et al (2020), Chawla and Joshi (2020), Hassan et al (2021) and Singh and Srivastava (2020). It shows that if consumers find the m-banking services beneficial, their perception of acceptance is high with the high level of familiarity with smartphones and their applications; this service is also perceived as easy and useful.…”
Section: Multiple Regression Analysissupporting
confidence: 90%
See 2 more Smart Citations
“…Our study found a significant relationship between PU and BI in line with the previous studies of Kumar et al (2020), Chawla and Joshi (2020), Hassan et al (2021) and Singh and Srivastava (2020). It shows that if consumers find the m-banking services beneficial, their perception of acceptance is high with the high level of familiarity with smartphones and their applications; this service is also perceived as easy and useful.…”
Section: Multiple Regression Analysissupporting
confidence: 90%
“…Our study found that PU, PEOU (Alalwan et al, 2018;Chawla & Joshi, 2020;Hassan et al, 2021;Kumar et al, 2020;Püschel et al, 2010;, CA (Alkhaldi, 2017;Hassan et al, 2021;Mutahar et al, 2018), PR (Gupta et al, 2017;Laukkanen & Kiviniemi, 2010;Mohapatra et al, 2020;Susanto et al, 2020) and PT (Engwanda, 2014;Kumar et al, 2020;Lin, 2011;Shankar et al, 2020;Tarhini et al, 2019) were found to be significant in m-banking adoption.…”
Section: Findings Discussion and Implicationsmentioning
confidence: 54%
See 1 more Smart Citation
“…The study uses a qualitative method and applies a systematic literature review to provide the necessary evidence for the promotion of digital financial services in China. Chawla and Joshi (2020) provide evidence of digital financial service adoption in the context of India and find an attitude as a significant predictor of mobile wallet adoption.…”
Section: Review Of Literaturementioning
confidence: 97%
“…This further influenced perceived satisfaction and recommendation to use mobile wallet services. In addition, and Chawla and Joshi (2020), besides identifying the antecedents which influence intention, also examined the mediation of trust, perceived usefulness and attitude to predict the intention to adopt a mobile wallet. Further, Shaw and Kesharwani (2019) used structural equation modelling and multi-group analysis to understand the importance and influence of PEOU, PU and subjective norms on mobile wallet adoption by young people.…”
Section: Review Of Literaturementioning
confidence: 99%